Stabilization of the electroweak scale in 3-3-1 models - Dias, Alex G.; Pleitez, V. [UNESP] (American Physical Society (APS), 2009)
One way of avoiding the destabilization of the electroweak scale through a strong coupled regime naturally occurs in models with a Landau-like pole at the TeV scale. Hence, the quadratic divergence contributions to the scalar masses are not considered as a problem anymore since a new nonperturbative dynamic emerges at the TeV scale. This scale should be an intrinsic feature of the models, and there is no need to invoke any other sort of protection for the electroweak scale. In some models based on the SU(3)CaS-SU(3)WaS-U(1)X gauge symmetry, a nonperturbative dynamics arise and it stabilizes the electroweak scale. © 2009 The American Physical Society.